A Cascaded Multilevel Inverter With Reduced Switch Count Using Modified Sinusoidal Pulse Width Modulation Technique - et. al., K.Aravinda Shilpa, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this article, the use of multilevel inverters is suggested by H-bridge. The recommended arrangement reduces the circuit size by the use of a reduced number of power switches and dc voltage sources. Simulation outcomes validate the efficiency and practical precision of the proposed topology using the new algorithm to produce all voltage levels for a 7-level inverter. For the two topologies obtained, it compares the percentage of THD.